Assessment and diagnosis of autism spectrum disorders in toddlers - Chawarska, Kasia; Saulnier, Celine A. (Henry Stewart Talks, 2011)
Clinical features of autism spectrum disorders, Patterns of onset of symptomatology in ASD, Early detection and diagnosis of ASD in the first two years of life, Multidisciplinary assessments and developmental profiles in ASD, Stability of diagnosis
Archived at 2022/04/27